2016
DOI: 10.3934/publichealth.2016.4.837
|View full text |Cite
|
Sign up to set email alerts
|

Housing for Female Factory Workers: The Association between Renting Accommodation and Satisfaction with Income and Living Conditions

Abstract: BackgroundVietnam has experienced a strong wave of migrants to urban and industrialized areas. This is a challenge for both local and national governments, which need to address the problems of the poor and socially marginalized, including providing housing for rural-to-urban migrants. Poor housing and the economic burden of house renting are increasingly recognized as determinants of both physical and mental health.ObjectivesThis paper examined the association between renting accommodation and income satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…A cross-sectional study was implemented by Nguyen's survey of 2818 female workers in 10 light manufacturing factories; only a few female workers (2.8%) said their income can meet family needs, while 14.4% of women said their salary is not enough to cover their day-to-day expenses. More than 28% of workers who had to rent accommodation claimed that their income was not even enough to cover this expenditure (18.5%) [101].…”
Section: Work-related Stressmentioning
confidence: 99%
“…A cross-sectional study was implemented by Nguyen's survey of 2818 female workers in 10 light manufacturing factories; only a few female workers (2.8%) said their income can meet family needs, while 14.4% of women said their salary is not enough to cover their day-to-day expenses. More than 28% of workers who had to rent accommodation claimed that their income was not even enough to cover this expenditure (18.5%) [101].…”
Section: Work-related Stressmentioning
confidence: 99%
“…A report from the United Nations Industrial Development Organization in 2015 revealed that in Vietnam, more than 2.3 million people worked in industrial zones, and 70% of them were migrant workers with a predominance of females and youth [23]. However, Quynh et al found that most of them rented accommodation with very poor quality and sanitation standards [24]. The extant literature on the relationship between health and internal labor migration in Vietnam has primarily examined a number of prevalent health risks, such as HIV/AIDS vulnerability and transmission [25,26,27], reproductive tract infection among female migrants [28,29], excessive alcohol consumption among male street laborers [30], sexual practices and sexually transmissible infections among migrant sex workers [31,32], or malaria incidence in the at-risk migrant population [33].…”
Section: Introductionmentioning
confidence: 99%
“…This gender preference is also reflected in the study's low proportion of male migrant workers in the garment industry, where less than one in every four participants is male. In Vietnam, this gender imbalance is prevalent in the garment and light manufacturing industries, such as shoemaking, seafood processing, and electrical device manufacturing (General Statistics Office of Vietnam, 2017; Nguyen et al, 2016). Among immigrant nursing assistants in the United States, a similar relationship between gender and turnover intention has been reported (Sloane et al, 2010).…”
Section: Discussionmentioning
confidence: 94%
“…These results showed that numerous factors other than income level affect migrant workers' satisfaction with their income. Compared to those who did not have to pay rent, female workers in Vietnam's industrial zones, for instance, had a higher percentage of income dissatisfaction (Nguyen et al, 2016). A recent study of workers in Vietnam's industrial zones found that migrant counterparts had higher monthly incomes and comparable housing conditions to non-migrant workers (Do et al, 2021).…”
Section: Discussionmentioning
confidence: 99%